2004
DOI: 10.1074/jbc.m408410200
|View full text |Cite
|
Sign up to set email alerts
|

Dual Phosphorylations Underlie Modulation of Unitary KCNQ K+ Channels by Src Tyrosine Kinase

Abstract: Src tyrosine kinase suppresses KCNQ (M-type) K ؉ channels in a subunit-specific manner representing a mode of modulation distinct from that involving G protein-coupled receptors. We probed the molecular and biophysical mechanisms of this modulation using mutagenesis, biochemistry, and both whole-cell and single channel modes of patch clamp recording. Immunoprecipitation assays showed that Src associates with KCNQ2-5 subunits but phosphorylates only KCNQ3-5. Using KCNQ3 as a background, we found that mutation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 43 publications
2
47
0
Order By: Relevance
“…Thus, we have shown clearly that SP-mediated enhancement of M current in DRG is PLC dependent and is inhibited by PTX, both supporting a role for GPCRs. Src also is widely reported to have an inhibitory effect on M channels, an effect mediated by phosphorylation of two tyrosines [e.g., Y67 and Y349 in Kv7.3 (54)(55)(56)]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, we have shown clearly that SP-mediated enhancement of M current in DRG is PLC dependent and is inhibited by PTX, both supporting a role for GPCRs. Src also is widely reported to have an inhibitory effect on M channels, an effect mediated by phosphorylation of two tyrosines [e.g., Y67 and Y349 in Kv7.3 (54)(55)(56)]. …”
Section: Discussionmentioning
confidence: 99%
“…PIP 2 depletion is the likely mechanism mediating the classic muscarinic inhibition of M-current (14-16), but other mechanisms, including phosphorylation, may contribute to channel modulation by other neurotransmitters (16). Indeed, KCNQ1 and KCNQ2 subunits associate with a variety of kinases and phosphatases via A-kinase anchor proteins (17)(18)(19)(20), and mutational studies implicate KCNQ2͞KCNQ3 phosphorylation sites for channel regulation by protein kinase A (PKA), protein kinase C (PKC), and src tyrosine kinase (10,19,21,22). KCNQ2 and KCNQ3 subunits possess large intracellular domains containing many additional potential phosphorylation sites (Fig.…”
mentioning
confidence: 99%
“…A previous co-immunoprecipitation analysis in CHO cells could detect a prominent association of Src with Q2 that was not less than that observed with Q3; however, Src-dependent tyrosine phosphorylation was only detected in Q3 (Li et al, 2004). However, in view of the reduction of Q2 currents mediated by Src in oocytes (Fig.…”
Section: Introductionmentioning
confidence: 93%
“…Intriguingly, two tyrosine residues located in opposite termini of the Q3 subunit have been shown to be involved in the Src action (Li et al, 2004), leading us to hypothesize that the modulation by Src might potentially involve crosstalk between the cytosolic termini, similar to the modulation by CaM and Syx. Furthermore, whereas in CHO cells Src has been reported to target Q3 and not Q2 , a study in HEK cells has suggested that Src mediates a tonic increase in Q2 channel function (Jow and Wang, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation